Equilibrium Price Modelling of an Affordable Housing in Malaysia - Ramli, Fazilah; Zainal, Rozlin; Ali, Maimunah (International Journal of Supply Chain Management, 2016)
The main purpose of this study is to propose the equilibrium price modelling for affordable housing in Malaysia. This paper examines whether the equilibrium price of affordable housing is strongly related with any affordable housing demand factors (house price, housing physical state, monetary status, population changes, location, and infrastructure amenities provided) and affordable housing supply factors (house price, cost of construction, land availability, population changes, location, and government interventions). The empirical data of housing prices are collected from Valuation and Property Services Department of the Ministry of Finance Malaysia from 1995 to 2015. Regression analysis is conducted to see the strength of relationship between the affordable housing demand and supply factors with the affordable housing equilibrium price. The paper is useful for buyer and private developers to know which factors lead to equilibrium price of affordable housing. This paper can serve as a guide for the government in controlling and stabilizing the affordable housing price.